Animacies : Biopolitics, Racial Mattering, and Queer Affect - Chen, Mel Y., 1969- (Book collections on Project MUSE., 2012)
Mel Y. Chen draws on studies of sexuality, race, and affect to consider how matter that is considered insensate, immobile, deathly, or otherwise ""wrong, "" animates cultural life in important ways.